The Timing of Biliary Surgery in Acute Pancreatitis - Ranson, John H. C. (1979)
The timing of biliary surgery remains controversial in patients with acute pancreatitis associated with cholelithiasis. Eighty hospital admissions for acute pancreatitis, occurring in 74 patients with cholelithiasis, have therefore been reviewed. Among 22 patients who underwent abdominal surgery during the first week of treatment, there were five deaths (23%) and four patients (18%) who required more than seven days of intensive care. Fifty-eight episodes of pancreatitis were managed nonoperatively during the first week of treatment, with no deaths, although six (10%) required more than seven days of intensive care. Biliary surgery was undertaken later during the same admission in 37 patients, with no deaths. Twenty-one patients were discharged without biliary operation, but seven (33%) developed further pancreatitis. Previously reported prognostic signs were used to divide pancreatitis into 57 “mild” episodes (1.8% mortality) and 23 “severe” episodes (17% mortality). Early (day 0-7) definitive biliary surgery was undertaken in 11 patients with “mild” pancreatitis, with one death (9%), and in six patients with “severe” pancreatitis, with four deaths (67%). In three recent patients with “severe” pancreatitis, early biliary surgery was limited to cholecystostomy, with no deaths. These findings suggest that although early correction of associated biliary disease may be undertaken safely in many patients with “mild” acute pancreatitis, early definitive surgery is hazardous in “severe” pancreatitis and should, if possible, be deferred until pancreatitis has subsided. In most patients biliary surgery should precede hospital discharge.